Instructional contingencies in a preschool classroom: What has been taught? (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
The aim of this study was to describe and characterize the instructional contingencies that occurred between teachers and preschool students (teachers’ instructions; responses evoked in students; consequences dispensed and their consistency). Ten videotapes of interactions between two teachers and 23 children (average of 2 years and 9 months old) from a public daycare center were transcribed and instructional episodes were categorized. Most of teachers' verbal responses were instructions (more than half “vocal”). The students followed approximately 70% of the instructions and, in 91% of the cases, presented non-verbal performances. Teachers showed consequences for these performances in an intermittent schedule of reinforcement, which was enough to guarantee engagement of the children. However, the absence of instructions with models and visual cues, the low frequency of corrections and the high rate of correct performances of the children suggest that the instructions requested performances known by the children, with few opportunities for learning a new repertoire.
Keywords: instructional control; verbal behavior; early childhood education